-5(k+3)+4k=3(k-5)

Simple and best practice solution for -5(k+3)+4k=3(k-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(k+3)+4k=3(k-5) equation:


Simplifying
-5(k + 3) + 4k = 3(k + -5)

Reorder the terms:
-5(3 + k) + 4k = 3(k + -5)
(3 * -5 + k * -5) + 4k = 3(k + -5)
(-15 + -5k) + 4k = 3(k + -5)

Combine like terms: -5k + 4k = -1k
-15 + -1k = 3(k + -5)

Reorder the terms:
-15 + -1k = 3(-5 + k)
-15 + -1k = (-5 * 3 + k * 3)
-15 + -1k = (-15 + 3k)

Add '15' to each side of the equation.
-15 + 15 + -1k = -15 + 15 + 3k

Combine like terms: -15 + 15 = 0
0 + -1k = -15 + 15 + 3k
-1k = -15 + 15 + 3k

Combine like terms: -15 + 15 = 0
-1k = 0 + 3k
-1k = 3k

Solving
-1k = 3k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-3k' to each side of the equation.
-1k + -3k = 3k + -3k

Combine like terms: -1k + -3k = -4k
-4k = 3k + -3k

Combine like terms: 3k + -3k = 0
-4k = 0

Divide each side by '-4'.
k = 0

Simplifying
k = 0

See similar equations:

| 80=5*2b | | -2-(6)= | | 25x+30y=120 | | .1(.1x+.9)= | | 3y=3y+18 | | -6(x-2)=12-3x | | 15+6x=25+5x | | 5x-2(-x-6)=-37 | | x^2=4x-6 | | 3+8q=5+7q | | 3x^2+4-10=0 | | x-174=-4x+1 | | 2m+10=16 | | Ei=5r+18 | | -16.04-(-9.57)= | | log(4x+1)+log(x+2)=1 | | 3m+(-10)=8m+(-10) | | -32.7+(-0.2)= | | 4t^2-28t+45=0 | | 8s-(5s+6)=.5(20+6) | | 6(7b+6)-(b+5)=-10 | | -.25x-2= | | E=5r+18 | | -4.75+2.19= | | +13-(+18)= | | 5.5=2+d | | 6(L+2)=36-6L | | 10-3x=-3(x-4) | | 13-18= | | 5(L+2)=36-5L | | 2y+15=19 | | -6.47-10.16= |

Equations solver categories